Advances in computer methods and geomechanics : IACMAG symposium 2019 (Lecture notes in civil engineering / editors Marco di Prisco [y otros seis] ;, 2020)
This volume presents selected papers from IACMAG Symposium,The major themes covered in this conference are Earthquake Engineering, Ground Improvement and Constitutive Modelling. This volume will be of interest to researchers and practitioners in geotechnical and geomechanical engineering.